2022
DOI: 10.3390/ijerph19063449
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Dentistry—Narrative Review

Abstract: Nowadays, artificial intelligence (AI) is becoming more important in medicine and in dentistry. It can be helpful in many fields where the human may be assisted and helped by new technologies. Neural networks are a part of artificial intelligence, and are similar to the human brain in their work and can solve given problems and make fast decisions. This review shows that artificial intelligence and the use of neural networks has developed very rapidly in recent years, and it may be an ordinary tool in modern d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 52 publications
0
31
0
3
Order By: Relevance
“…In endodontics, artificial intelligence is gaining more relevance [ 14 ]. Its significance in endodontic treatment planning and disease diagnosis is growing at the moment [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…In endodontics, artificial intelligence is gaining more relevance [ 14 ]. Its significance in endodontic treatment planning and disease diagnosis is growing at the moment [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…Artificial intelligence (AI) is gaining importance in the fields of medicine and dentistry nowadays [ 13 ]. It can be useful in a variety of situations where new technologies might benefit and help people.…”
Section: Methodsmentioning
confidence: 99%
“…The input layer is where information enters the system, and the hidden layer is where the data are processed (where the system decides what to do). NNs may outline any input to output given a set of mathematical models if there is enough data, a lot of data [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various valuable narrative reviews were published that concluded that the AI approach to imaging technology is profoundly changing the established protocols of diagnosis in dentistry [ 4 , 5 , 26 , 62 , 63 , 64 ]. The application of AI in healthcare is an area of significant attention and importance.…”
Section: Introductionmentioning
confidence: 99%